2003
DOI: 10.1046/j.1440-1614.2003.01197.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Outcome Following Brief Psychodynamic-Interpersonal Therapy for Deliberate Self-Poisoning

Abstract: Four session PIT for deliberate self-poisoning is effective in reducing suicidal ideation in patients with less severe depression, no prior history of self-harm, and who have not consumed alcohol with the overdose. Extended therapy may be indicated for those with more severe depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 19 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…Consi derable evidence points to the complexity of the psychotherapeutic treatment of suicidal patients (1)(2)(3)(4). A number of structured protocols have been developed to treat suicidality, including cognitive behavior problemsolving therapy (5)(6)(7)(8), dialectical behavior therapy (1,9,10), time-limited interpersonal psychotherapy (11), and brief psychodynamic psychotherapy (12). Although some evidence exists for the efficacy of such protocols for selected patient groups, in our experience of supervising, consulting with, and studying clinicians who treat suicidal patients, we have found that most clinicians employ a relatively open-ended, eclectic psychotherapeutic approach that incorporates cognitive behavior and interpersonal techniques and varying degrees of reliance on psychodynamic principles.…”
Section: (Am J Psychiatry 2006; 163:67-72)mentioning
confidence: 99%
“…Consi derable evidence points to the complexity of the psychotherapeutic treatment of suicidal patients (1)(2)(3)(4). A number of structured protocols have been developed to treat suicidality, including cognitive behavior problemsolving therapy (5)(6)(7)(8), dialectical behavior therapy (1,9,10), time-limited interpersonal psychotherapy (11), and brief psychodynamic psychotherapy (12). Although some evidence exists for the efficacy of such protocols for selected patient groups, in our experience of supervising, consulting with, and studying clinicians who treat suicidal patients, we have found that most clinicians employ a relatively open-ended, eclectic psychotherapeutic approach that incorporates cognitive behavior and interpersonal techniques and varying degrees of reliance on psychodynamic principles.…”
Section: (Am J Psychiatry 2006; 163:67-72)mentioning
confidence: 99%
“…Several studies have reported on the efficacy (or otherwise) in the follow-up period immediately after cessation of different interventions, for suicidal behaviours of different sorts in different clinical populations: Dialectical Behaviour Therapy for parasuicide (Linehan et al, 1993), mentalization therapy in a day hospital program for suicide attempt and self-harm (Bateman & Fonagy, 2001), "caring letters" for suicide mortality (Motto & Bostrom, 2001), psychodynamic-interpersonal therapy for hospital-treated DSH (Guthrie et al, 2003), and postcards for hospital-treated DSP (Carter et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It seems that psychodynamic treatment which focuses mainly on basic relational and emotional processes does not interact with these variables. Similar results of missing relationships between sociodemographic variables and the outcome of psychodynamic psychotherapy were found in the treatment of depression (Bastos, Guimaraes, & Trentini, ), social anxiety disorder (Wiltink et al ., ), and deliberate self‐poisoning (Guthrie et al ., ). However, these findings are not entirely consistent.…”
Section: Discussionmentioning
confidence: 97%
“…However, it seems that the positive correlation between higher baseline symptom severity occurs in long-term therapies unlike short-term therapies where this correlation is found to be negative. For example, higher pre-treatment symptom severity in the psychodynamic treatment of social anxiety (mean duration of the treatment 37.4 weeks) was found to be positively related to the outcome of the therapy (Wiltink et al, 2016), whereas symptom severity in the shortterm psychodynamic treatment of depression (Marttunen et al, 2008), or in brief psychodynamic-interpersonal therapy for deliberate self-poisoning (Guthrie et al, 2003) was related negatively.…”
Section: Discussionmentioning
confidence: 99%